Medical Image Analysis Using Deep Learning and Distribution Pattern Matching Algorithm - Jaber M.M.; Yussof S.; Elameer A.S.; Weng L.Y.; Abd S.K.; Nayyar A. (Tech Science Press, 2023)
Automation; Complex networks; Computational complexity; Deep learning; Image analysis; Medical imaging; Pattern matching; Pixels; Distribution pattern-matching rule; Distribution patterns; Gray wolf-optimized deep convolution network; Gray wolves; Learning patterns; Matching rules; Medical fields; Medical image analysis; Pattern matching algorithms; Pattern-matching; Convolution